'The natives are always stealing': White, vigilantes and the 'reign of terror' in the Orange Free State, 1918-1924 - Murray, Martin J. (The journal of African history, 1989)
During the formative years of capitalist agriculture, white farmers in the Orange Free State relied on both legal and extra-legal means to create a docile labour force of African workers. The article looks at the violence committed by the white vigilante groups against the African workers. While the state authorities never officially sanctioned vigilantism, these white farmers who used violence to intimidate their African labourers had little to fear with respect to prosecution, let alone conviction. (DÜI-Sen)